2016
DOI: 10.1111/phpp.12244
|View full text |Cite
|
Sign up to set email alerts
|

The clinical severity score of chronic actinic dermatitis correlates with in vivo photoallergic reactions and the immunologic parameters related to a shift towards Th2 immunity from the Th2/Th1 balanced status in patients with chronic actinic dermatitis

Abstract: The CSS-CAD correlates with total IgE level, PB eosinophil count and a shift towards Th2 immunity from Th2/Th1. So we suggest the Th1/Th2 dysbalance may be affected by the CSS-CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 27 publications
(30 reference statements)
1
23
0
Order By: Relevance
“…However, durable and long-lasting responses reveal that dupilumab targets vital inflammatory pathways of atopic dermatitis (AD) and other Th2 cell-mediated inflammatory skin diseases, such as CAD, As Ko et al have recently suggested that T cells may play a role in the dysbalance of Th1/Th2 in CAD, in atopic dermatitis, there is an over-activation of the Th2 in the acute stage. However, the chronic phase is manifested by Th1 immune response and sustained Th2 -cells activation ( 12 , 13 ). According to the study, UVB-induced CD3+, CD4+, and CD8 − regulatory T cells suppress the immune system through the release of the immune-regulatory cytokines IL-4 and IL-10 ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, durable and long-lasting responses reveal that dupilumab targets vital inflammatory pathways of atopic dermatitis (AD) and other Th2 cell-mediated inflammatory skin diseases, such as CAD, As Ko et al have recently suggested that T cells may play a role in the dysbalance of Th1/Th2 in CAD, in atopic dermatitis, there is an over-activation of the Th2 in the acute stage. However, the chronic phase is manifested by Th1 immune response and sustained Th2 -cells activation ( 12 , 13 ). According to the study, UVB-induced CD3+, CD4+, and CD8 − regulatory T cells suppress the immune system through the release of the immune-regulatory cytokines IL-4 and IL-10 ( 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…proposed the concept of photosensitive atopic dermatitis, the clinical features of which include atopic diathesis, eczematous lesions in UV radiation‐exposed body regions and positive photoprovocation reactions, which may be misdiagnosed as CAD. IgE levels were reported to be higher in the severe CAD group than in the others, and are considered to be related to a shift towards T‐helper (Th)2 immunity from the Th2/Th1 balance status 11,12 . In our study, patient 3 had higher IgE levels and positive patch tests to metals, which may also be related to the rapid recurrence of symptoms.…”
Section: Discussionmentioning
confidence: 49%
“…However, a mechanism of delayed-type hypersensitivity to a UV-induced autoantigen or a contact allergy to exogenous allergens may be inferred. 9 Ko et al 2 found that Th1/Th2 dysbalance may be closely related to the onset of CAD.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Although the pathophysiology of CAD is not well known, it has been claimed that a Th1/Th2 dysbalance caused by suppressor T cells may play a role in the occurrence of CAD. 2 In some recalcitrant cases, conventional treatments based on photoprotection, topical steroids, and immunosuppressive agents are disappointing. Recently, dupilumab, a human monoclonal antibody developed for dampening Th2 signaling and inhibiting the effects of IL-4 and IL-13, 3 has shown promising results in small series and case reports on CAD.…”
Section: Introductionmentioning
confidence: 99%